PENGUKURAN ASPEK KEPUASAN KONSUMEN LE FLUFFY DESSERT - Liliana Dewi; Stella Nathania (Jurnal Bisnis Terapan, 2018)
The food industry keeps on growing due to the needs of each individual for food to survive. The purpose of this research is to determine the influence of aesthetics, serviceability, perceived quality and durability on the customer satisfaction of Le Fluffy Dessert. Population in this study is customers who already bought product of Le Fluffy Dessert. The number of the population is 53 people. The sampling technique used is saturated sampling. This research uses total of 53 Le Fluffy Dessert customers as the samples. The data are collected using questionnaire. The technique analysis used in this research is multiple linear regression analysis. The results show that aesthetics and serviceability have no significant effect on the customer satisfaction of Le Fluffy Dessert. The results also show that perceived quality and durability significantly affect the customer satisfaction of Le Fluffy Dessert.